2017
DOI: 10.1371/journal.pone.0170971
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Insulin Level in Selecting Fortified Diet-Fed, Streptozotocin-Treated Rat Model of Type 2 Diabetes for Anti-Diabetic Studies

Abstract: BackgroundPathophysiological investigation of disease in a suitable animal model is a classical approach towards development of a credible therapeutic strategy. This study examined appropriate insulin level in selecting animal model for type 2 diabetes (T2D) studies.MethodAlbino Wistar rats (150-200g) were divided into two groups fed with commercially available normal-diet-feed (NDF) and water or fortified diet feed (FDF) (10g NDF per gram of margarine) with 20% fructose solution as drinking water. After 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
(109 reference statements)
2
30
0
Order By: Relevance
“…STZ may increase the production of ROS and inhibit enzyme activities related with the scavenging of free radical [12]. Intraperitoneal administration of STZ (45-55 mg/kg body weight) decreased insulin sensitivity and induced hyperglycemia and diabetes mellitus in mice and rats [13,14]. At the same time, several studies have been conducted with natural antioxidants for the prevention of oxidative damage under high oxidative stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…STZ may increase the production of ROS and inhibit enzyme activities related with the scavenging of free radical [12]. Intraperitoneal administration of STZ (45-55 mg/kg body weight) decreased insulin sensitivity and induced hyperglycemia and diabetes mellitus in mice and rats [13,14]. At the same time, several studies have been conducted with natural antioxidants for the prevention of oxidative damage under high oxidative stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, type 2 diabetes (T2D) was successfully induced in animals by feeding them either a high‐fat diet (HFD) that resulted in glucose intolerance with impaired pancreatic function and hypercholesterolemia, [ 8 ] or a high‐fructose diet that induced hypertriglyceridemia and hyperinsulinemia. [ 9 ] In animal models using both diet regimens, the blood glucose levels of diabetic rats could not be reached and it failed the validation of antidiabetic drugs. [ 10 ] In addition, the IR of T2D could not be induced using low doses of streptozotocin (STZ).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in the model simulating the phenotype and the pathogenesis of human T2D. [9] Dapagliflozin (DAPA) is a sodium-glucose cotransporter 2 (SGLT2) inhibitor that was developed to treat T2D. [12] As DAPA is insulin-independent, any stage of T2D with severe IR or β-cell disfunction could be effectively treated using SGLT2 inhibitors.…”
mentioning
confidence: 99%
“…It is reported that ROS have considered as one of the primary mediators in insulin resistance . Many studies reported that hyperinsulinemia is associated with diet and observed in fructose or high fat intake animal models of insulin resistance, metabolic syndrome and type 2 diabetes …”
Section: Introductionmentioning
confidence: 99%
“…[4] Many studies reported that hyperinsulinemia is associated with diet and observed in fructose or high fat intake animal models of insulin resistance, metabolic syndrome and type 2 diabetes. [5][6][7] Recently, the increase in the use of refined food, which is rich fructose, has raised concerns about the potential adverse on public health. The metabolic pathway of fructose is associated with hepatic gluconeogenesis and lipid biogenesis.…”
Section: Introductionmentioning
confidence: 99%